MANAJEMEN INOVASI PEMBELAJARAN DI PERGURUAN TINGGI - Nur Arifin (Universitas Nurul Jadid, 2020)
The development of technology and information brings progress in all lines of life, including education. Lecturers must be able to keep up with the times by changing conventional learning strategies with innovative learning strategies. Several choices of innovative learning strategies based on the student centered learning approach include small group discussions, roleplay and simulation, discovery learning, cooperative learning, contextual learning, problem based learning, collaborative learning, and so on. The overall learning strategy places students or students at the center of learning, who are independent and active in finding learning resources, and are able to identify their own learning needs.